2010
DOI: 10.1111/j.1365-2567.2010.03376.x
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic modelling of cytokine polarization in the lung

Abstract: SummaryThe lung is one of the commonest sites of exposure to environmental allergen or pathogen, so the expression of a variety of cytokines in the lung is dynamically regulated by inflammatory or structural cells in the lung. In the last decades, characterization of the local lung cytokine milieu in allergic or injury models has identified a collective role of certain cytokines, such as type 1 or type 2 cytokines, driving polarized inflammatory and tissue phenotypes. With the development of transgenic mouse m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…1, Supplementary Figs. 32,33). LRT treatment in vitro has been demonstrated to inhibit calcium influx and subsequently induce ER stress, resulting in the calreticulin upregulation and CD47 protein down-regulation in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1, Supplementary Figs. 32,33). LRT treatment in vitro has been demonstrated to inhibit calcium influx and subsequently induce ER stress, resulting in the calreticulin upregulation and CD47 protein down-regulation in cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokines are essential in the host defense against invading pathogens as the products of immune signaling activation. The secretion of cytokines and related immune response constitutes the fundamentals of host defense, and tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), interferon-γ (IFN-γ), and interleukin-6 (IL-6) are the predominant cytokines of innate immunity in the protection against a majority of lung diseases 33 . it has been widely reported that M1 polarization of macrophages is essential in the antitumor immune response, and various kinds of cytokines secreted by macrophages play dominant roles in regulating intracellular communication and killing cancer cells 34 .…”
Section: In Vitro Activation Of Macrophages' Antitumor Response By Lr...mentioning
confidence: 99%